(untitled) (Journal of Fiber Bioengineering and Informatics, 2009)
Through the comparison and analysis of the angiogenesis conditions for different pathophysiologic states, such as growing process of the animal, tumor growth, and wound repair, an index of the hypoxia intensity is proposed to evaluate the environment of angiogenesis, based on which the mechanism of the angiogenesis patterns under different environment is discussed. A new concept of response effect is deduced for describing the reaction of the endothelial cell (EC)s towards the VEGF concentration in the microenvironment during the angiogenesis, and an explanation for different angiogenesis patterns of capillaries is given. At the same time the biological proofs cited from recent studies are provided to prove the response effect of the EC. With the results we try to show that in the pathophysiologic environment with high hypoxia intensity, the angiogenesis comes into being mainly by sprouting; while the hypoxia intensity is low, the angiogenesis mainly occurs through the intussusception. This concept shall offer a new basis and idea for the study of the capillary network construction, related clinical therapy, and induction of vascularization in the biomaterials.